Flow-injection spectrophotometric determination of azithromycin in pharmaceutical formulations using p-chloranil in the presence of hydrogen peroxide - Rufino, Jose Luiz [UNESP]; Pezza, Helena Redigolo [UNESP]; Pezza, Leonardo [UNESP] (Japan Soc Analytical Chemistry, 2008)
A flow-injection (FI) spectrophotometric procedure exploiting merging zones is proposed for the determination of azithromycin in pharmaceutical formulations. The method is based on the reaction of azithromycin with tetrachloro-phenzoquinone (p-chloranil) accelerated by hydrogen peroxide and conducted in a methanol medium, producing a purple-red color compound (lambda(max) = 540 nm). The FI system and the experimental conditions were optimized using a multivariate method. Beer's law is obeyed in a concentration range of 50 - 1600 mu g mL(-1) with an excellent correlation coefficient (r = 0.9998). The detection limit and the quantification limit were 6.6 and 22.1 mu g mL(-1), respectively. No interference was observed from the common excipients, and the recoveries were within 98.6 to 100.4%. The procedure was applied to the determination of azithromycin in pharmaceuticals with a high sampling rate (65 samples h(-1)). The results obtained by the proposed method were in good agreement with those obtained by the comparative method at 95% confidence level.